Cobalt Thiolates with Organic N, N, S-Tridentate Ligand: Conversion of Thiolate Complex to Sulfinate Complex via Sulfenate. Issue 1 (April 2020) - Kotera, Takanori; Fujita, Atsushi; Mikuriya, Masahiro; Yoshioka, Daisuke; Shibahara, Takashi; Nishimoto, Kichisuke; Handa, Makoto
Abstract: Mononuclear cobalt(III) complex with 2-[(3-aminopropyl)amino]ethanethiol (Hapaet), [Co(apaet)2 ]ClO4 (1 ) and the sulfinate complex, [Co(apaetO2 )2 ]ClO4 (2 ) were synthesized and characterized by measurements of the elemental analysis, infrared and electronic spectra (UV-vis-NIR), and temperature dependence of magnetic susceptibilities (4.5—300 K), and DFT calculations. X-Ray crystal structure analysis of 1 and 2 revealed an octahedral CoS2 N4 or Co(SO2 )2 N4 chromophore with meridional chelation of two apaet − or apaetO2 − . Conversion of 1 to the sulfinate complex 2 via the sulfenate complex was investigated by UV-vis spectra. Oxidation reaction of capsanthin with 1 was also examined.